2014
DOI: 10.1111/ijd.12418
|View full text |Cite
|
Sign up to set email alerts
|

HLA DRB1* and DQB1* alleles are associated with disease severity in patients with pemphigus vulgaris

Abstract: The HLA DRB1* and DQB1* alleles influence susceptibility to PV and may contribute to PV severity and type. These results suggest that genetic background may contribute to disease outcome by affecting the disease course and efficacy of treatment because some of the alleles were found significantly more frequently in patients with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
2
24
1
1
Order By: Relevance
“…Pemphigus vulgaris also echoes the pattern that autoimmune diseases occur more frequently in patients with another autoimmune disease and has associations with the female-predominant thyroid diseases and rheumatoid arthritis (Ameri et al, 2013, Gupta et al, 2011, Ljubojevic and Lipozencic, 2012, Svecova et al, 2014). Worsened outcome of PV has also been associated with females, as one recent analysis showed that the HLA alleles DRB1*04:02 and DQB1*03:02 were associated with severe PV, and DQB1*03:02 was found more frequently in female patients than in males (Svecova et al, 2014). However, no epidemiological studies to date have evidenced the association of sex with this genetic predisposition.…”
Section: Epidemiology and Etiologymentioning
confidence: 78%
“…Pemphigus vulgaris also echoes the pattern that autoimmune diseases occur more frequently in patients with another autoimmune disease and has associations with the female-predominant thyroid diseases and rheumatoid arthritis (Ameri et al, 2013, Gupta et al, 2011, Ljubojevic and Lipozencic, 2012, Svecova et al, 2014). Worsened outcome of PV has also been associated with females, as one recent analysis showed that the HLA alleles DRB1*04:02 and DQB1*03:02 were associated with severe PV, and DQB1*03:02 was found more frequently in female patients than in males (Svecova et al, 2014). However, no epidemiological studies to date have evidenced the association of sex with this genetic predisposition.…”
Section: Epidemiology and Etiologymentioning
confidence: 78%
“…Our study confirms that HLA DRB1* and HLA DQB1* alleles influence susceptibility to PF, but whether they have an effect on disease severity is questionable. Svecova et al . proposed that these alleles may also contribute to disease severity of the more common variant, PV.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that HLA DRB1* and HLA DQB1* alleles influence susceptibility to PF, but whether they have an effect on disease severity is questionable. Svecova et al 17 proposed that these alleles may also contribute to disease severity of the more common variant, PV. However, in a previous study, 18 our group did not find any link in HLA DRB1* or DQB1* allele frequency with prognosis for either PV or PF.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is multifactorial and various environmental factors have been implicated as triggering agents . Like many other autoimmune disorders, PV belongs to the family of polygenic disorders with phenotypes resulting from alterations in several different genes encoding molecules involved in the effector or regulatory functions in the immune system, with additive or interacting effects . However, inheritance of certain human leukocyte antigen (HLA) alleles is believed to be the most probable predisposing factor .…”
Section: Introductionmentioning
confidence: 99%
“…Like many other autoimmune disorders, PV belongs to the family of polygenic disorders with phenotypes resulting from alterations in several different genes encoding molecules involved in the effector or regulatory functions in the immune system, with additive or interacting effects . However, inheritance of certain human leukocyte antigen (HLA) alleles is believed to be the most probable predisposing factor . Most literature on the genetic susceptibility to PV is focused on the investigation of major HLA genes .…”
Section: Introductionmentioning
confidence: 99%